Expansion of the genetic toolkit for metabolic engineering of Clostridium pasteurianum: chromosomal gene disruption of the endogenous CpaAI restriction enzyme - Pyne, M. E.; Moo-Young, M.; Chung, D. A.; Chou, C. P. (Biotechnology for Biofuels, 2014)
Background: Clostridium pasteurianum is one of the most promising biofuel producers within the genus Clostridium owing to its unique metabolic ability to ferment glycerol into butanol. Although an efficient means is available for introducing foreign DNA to C. pasteurianum, major genetic tools, such as gene knockout, knockdown, or genome editing, are lacking, preventing metabolic engineering of C. pasteurianum. Results: Here we present a methodology for performing chromosomal gene disruption in C. pasteurianum using the programmable lactococcus Ll.ltrB group II intron. Gene disruption was initially found to be impeded by inefficient electrotransformation of Escherichia coli-C. pasteurianum shuttle vectors, presumably due to host restriction. By assessing the ability of various vector deletion derivatives to electrotransform C. pasteurianum and probing the microorganism's methylome using next-generation sequence data, we identified a new C. pasteurianum Type I restriction-methylation system, CpaAII, with a predicted recognition sequence of 5'-AAGNNNNNCTCC-3' (N = A, C, G, or T). Following rescue of high-level electrotransformation via mutation of the sole CpaAII site within the shuttle vectors, we retargeted the intron to the cpaAIR gene encoding the CpaAI Type II restriction endonuclease (recognition site of 5'-CGCG-3'). Intron insertion was potentially hindered by low retrohoming efficiency, yet this limitation could be overcome by a procedure for enrichment of the intron insertion. The resulting Delta cpaAIR mutant strain was efficiently electrotransformed with M. FnuDII-unmethylated plasmid DNA. Conclusions: The markerless and plasmidless Delta cpaAIR mutant strain of C. pasteurianum developed in this study can serve as a general host strain for future genetic and metabolic manipulation. Further, the associated gene disruption protocol should not only serve as a guide for chromosomal gene inactivation studies involving mobile group II introns, but also prove invaluable for applying metabolic engineering strategies to C. pasteurianum.